1986
DOI: 10.1007/bf01260921
|View full text |Cite
|
Sign up to set email alerts
|

Effects of afternoon injections of O-acetyl-5-methoxytryptophol, melatonin or 5-methoxytryptophol in female syrian hamsters

Abstract: Female Syrian hamsters were maintained in a 14:10 light: dark photoperiod (lights on 6 a.m.) and injected each afternoon between 4 p.m. and 6 p.m. with diluent or with 25 micrograms melatonin, O-acetyl-5-methoxytryptophol (aML) or 5-methoxytryptophol (ML). After 7 or 12 weeks of treatment, only the melatonin-treated hamsters were acyclic. Gross inspection of their ovaries revealed that they were smooth, brown, and devoid of corpora lutea and large follicles. Progesterone levels of the acyclic animals were midw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Essentially, this is what was observed in the present set of experiments. Melatonin injections inhibit estrous cyclicity and fecundity in female hamsters; the large, brown ovaries of these acyclic females are full of interstitial tissue (Richardson et al, 1982) but still produce some progesterone (Little et al, 1986). The observed depression in relative spleen weights associated with small uteri conforms to the paradigm of hypogonadism also in that sex.…”
Section: Resultsmentioning
confidence: 58%
“…Essentially, this is what was observed in the present set of experiments. Melatonin injections inhibit estrous cyclicity and fecundity in female hamsters; the large, brown ovaries of these acyclic females are full of interstitial tissue (Richardson et al, 1982) but still produce some progesterone (Little et al, 1986). The observed depression in relative spleen weights associated with small uteri conforms to the paradigm of hypogonadism also in that sex.…”
Section: Resultsmentioning
confidence: 58%
“…This almost forgotten metabolite (Fig. 2) was reported to inhibit nicotinic and muscarinic acetylcholine receptors [26] and, in Syrian hamsters, to decrease pituitary prolactin and LH levels [76], but again, these effects are presumably only of pharmacological nature. This compound is very unstable in the presence of ubiquitously abundant esterases [72].…”
Section: Melatonin Deacetylationmentioning
confidence: 99%
“…Studies have also suggested that pulmonary capillary endothelial cells can stimulate epithelial progenitor cells, including bronchoalveolar stem cells and alveolar epithelial cells, to proliferate, promoting alveolar regeneration by producing paracrine growth factors ( 238 ). EPC therapy is also considered a potential treatment for cell-based pulmonary hypertension ( 239 , 240 ). These cell-based therapy strategies may inspire the treatment of COVID-19.…”
Section: Stem Cell Therapy and Covid-19mentioning
confidence: 99%